Jonathan Livingston Seagull - Bach, Richard; Munson, Russell (New York : Scribner, 2006)
An unusual seagull becomes an outcast from his flock because of his search for a higher purpose in life and his quest for more freedom.
Young Adult
Keywords: Gulls -- Fiction; Gulls -- Fiction